2017
DOI: 10.1002/ceat.201600671
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Activity of Synthetic N‐doped TiO2/Reduced Graphene Oxide Crystalline Composites

Abstract: N-doped TiO 2 /reduced graphene oxide (N-TiO 2 /RGO) composites were prepared by a hydrothermal method. Characterization and photocatalytic tests showed that the N-TiO 2 /RGO composites were more efficient for degrading effluents in comparison with the pure TiO 2 powders and the N-doped TiO 2 powders. The photocatalytic performance of the composites was enhanced with the increase of the reduced graphene oxides' content, whose degradation rate constant was higher than that of N-TiO 2 under simulated sunlight ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Degradation is accomplished due to the presence of highly reactive OH, O 2 − , and O 3 , which are produced by imposing UV or sunlight onto the photocatalyst surface. The irradiated wavelength highly relies on the band gap energy of the employed photocatalyst . Conventional photocatalysts like TiO 2 and ZnO were used in many degradation processes, and scientists are trying to improve their efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Degradation is accomplished due to the presence of highly reactive OH, O 2 − , and O 3 , which are produced by imposing UV or sunlight onto the photocatalyst surface. The irradiated wavelength highly relies on the band gap energy of the employed photocatalyst . Conventional photocatalysts like TiO 2 and ZnO were used in many degradation processes, and scientists are trying to improve their efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Composite materials consisting of two or more materials are widely used in many industrial fields . Selecting desirable combinations of materials can produce various properties.…”
Section: Introductionmentioning
confidence: 99%
“…36 It was confirmed that the RGO-TiO 2 nanocomposites exhibited an agglomerated morphology and less synergy effect between RGO and TiO 2 due to the severe aggregation of GO layers. 37 In addition, the spherical TiO 2 nanoparticles were liable to agglomerate. Thus, poor interfacial contact between RGO and TiO 2 lead to the low photocatalytic activity of RGO-TiO 2 composites.…”
mentioning
confidence: 99%